Combined stool-based multiplex PCR and microscopy for enhanced pathogen detection in patients with persistent diarrhoea and asymptomatic controls from Côte d'Ivoire. (June 2015) - Becker, S.L.; Chatigre, J.K.; Gohou, J.-P.; Coulibaly, J.T.; Leuppi, R.; Polman, K.; Chappuis, F.; Mertens, P.; Herrmann, M.; N'Goran, E.K.; Utzinger, J.; von Müller, L.
Abstract: Infectious diarrhoea ranks among the leading causes of morbidity worldwide. Although most acute diarrhoeal episodes are self-limiting, the diagnosis and treatment of persistent diarrhoea (≥2 weeks) are cumbersome and require laboratory identification of the causative pathogen. Stool-based PCR assays have greatly improved the previously disappointing pathogen detection rates in high-income countries, but there is a paucity of quality data from tropical settings. We performed a case–control study to elucidate the spectrum of intestinal pathogens in patients with persistent diarrhoea and asymptomatic controls in southern Côte d'Ivoire. Stool samples from 68 patients and 68 controls were obtained and subjected to molecular multiplex testing with the Luminex ® Gastrointestinal Pathogen Panel (GPP), microscopy and rapid antigen detection tests for the diagnosis of diarrhoeagenic pathogens. Overall, 20 different bacteria, parasites and viruses were detected by the suite of diagnostic methods employed. At least one pathogen was observed in 84% of the participants, and co-infections were observed in >50% of the participants. Enterotoxigenic Escherichia coli (32%), Giardia intestinalis (29%) and Shigella species (20%) were the predominant pathogens, and Strongyloides stercoralis (10%) was the most prevalent helminth. Pathogen frequencies and numbers of co-infections were similar in patients and controls. Although the Luminex ® GPP detects a broad range of pathogens, microscopy for helminths and intestinal protozoa remains necessary to cover the full aetiological spectrum in tropical settings. We conclude that highly sensitive multiplex PCR assays constitute a useful screening tool, but that positive results might need to be confirmed by independent methods to discriminate active infection from asymptomatic faecal shedding of nucleic acids.